"POLICY SHIFTS AND THEIR IMPACT ON THE AMERICAN MUSLIM COMMUNITY: A COMPARATIVE ANALYSIS OF THE BUSH AND OBAMA ADMINISTRATIONS" - Thomas, Daniel Mitchell (Top Journal of Public Policy and Administration (TJPPA), 2023)
In the wake of the September 11 attacks, the American Muslim community experienced significant shifts in government policies that profoundly affected their lives and sense of belonging within the United States. This study offers a comparative analysis of how the Bush and Obama administrations approached issues of national security and terrorism, and the subsequent impact on the American Muslim community. The Bush administration, in response to the 9/11 attacks, implemented a series of legislative measures, notably the Patriot Act. These measures not only restricted visas but also permitted the federal government to employ racial profiling as a tool for arresting suspected terrorists. Furthermore, the FBI was granted increased surveillance authority over Muslim American citizens. These policies left the American Muslim community feeling marginalized and demoralized. In contrast, the Obama administration adopted a different approach to national security and terrorism. Although the Obama administration had only governed for a short time when this study was conducted, there were discernible shifts in policy that seemed to have a more positive impact on the American Muslim community. For example, the Obama administration championed the right of Muslims to establish organizations and mosques across the United States, including the controversial "Ground Zero" Mosque. Additionally, efforts were made to prevent the burning of the Qur’an, a gesture that helped prevent the escalation of negative sentiments within the American Muslim community. The American Muslim community responded differently to the policies of these two administrations. The Bush administration’s measures led to a distancing of the Muslim community from the Republican Party, while many members of the American Muslim community placed their hope in President Obama’s commitment to positive change. This research aims to provide a comprehensive analysis of the distinct impacts of government policies on the American Muslim community in the post-9/11 era. By examining the policies and their consequences during both the Bush and Obama administrations, this study seeks to shed light on the evolving relationship between the American Muslim community and the U.S. government. In conclusion, this study underscores the importance of understanding the evolving dynamics between government policies and the American Muslim community, particularly in the context of national security and counterterrorism efforts. By comparing the approaches of the Bush and Obama administrations, we can gain valuable insights into the complex interplay between policy decisions and the experiences of this community in the United States